Atherosclerosis and arteriosclerosis: two case reports of CBCT incidental findings - Carneiro, Ana Luiza Esteves (2023)
Different types of vascular calcifications can be observed as incidental findings on Cone Beam Computed Tomography (CBCT) images. Atherosclerosis consists of atherosclerotic plaque accumulation, an inflammatory condition that can result in the narrowing of the blood vessel lumen. On the other hand, arteriosclerosis is the hardening of the artery wall, and Mönckeberg’s arteriosclerosis, a non-obstructive calcification of medium and small-sized muscular arteries, is the most common type of arteriosclerosis. The aim of this paper is to report two cases of soft tissue calcifications observed on CBCT images. Case report 1: a 75-year-old female patient was scanned on CBCT unit KaVo OP 3D Pro for implant planning, and a unilateral radiopacity presenting high density and irregular shape was observed on soft tissues, located inferiorly and internally to the right gonial angle of the mandible, suggesting a calcified carotid atheroma. Case report 2: a 60-year-old female patient was scanned on CBCT unit KaVo OP 3D Pro for implant planning, and bilateral radiopacities presenting circular and elongated shapes with radiolucent interior and tortuous course were observed on soft tissues of the buccal aspect of the mandible, suggesting Mönckeberg’s arteriosclerosis of the facial vasculature. Even though these soft tissue calcifications do not require specific treatment, their presence is commonly associated with patients at risk of cardiovascular and cerebral complications. Therefore, their recognition on CBCT images is of great importance, being the dental practitioner’s responsibility to ensure a timely referral to the patient’s medical physician for further assessment.